The Trade Competitiveness of the Indonesian Automotive Industry - Pauline H.P. Tan (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
The automotive industry is one of the leading sectors that has a significant contribution to the national economy. The automotive sector has contributed an investment value of IDR 99.16 trillion with a total production capacity of 2.35 million units per year and has absorbed a direct workforce of 38.39 thousand people. From a job creation standpoint, the automotive sector has a far-reaching impact on the more than 1.5 million people working along the industry's value chain. The automotive industry has an essential and strategic role, so it is included in the Making Indonesia 4.0 roadmap, which is prioritized for development in the implementation of industry 4.0. Since 2020, domestically produced motor vehicle products have been able to penetrate the export market to more than 80 countries around the world. On this basis, it is essential for Indonesia to be able to measure the comparative advantage of the Indonesian automotive industry, or to measure the competitiveness of Indonesian automotive products in the world market. This competitiveness measurement uses Revealed Comparative Advantage (RCA), which measures Indonesia's comparative advantage using an index known as the Balassa Index.